Konsep Dasar Media Pembelajaran - Juhaeni; Safaruddin; R Nurhayati; Aulia Nur Tanzila (IAI Al Khoziny Buduran Sidoarjo, 2020)
This article aims to describe the basic concepts of learning media which include: learning as a communication process, the definition of the concept of learning media, the function of learning media, the basis for using learning media, the characteristics of learning media.